Earthquack! - Palatini, Margie (Simon & Schuster Books for Young Readers, 2002)
When Chucky Ducky feels the earth beneath him grumble and rumble, he runs to alert the other barnyard animals to the coming earthquake, but just as a wily weasel is about to take advantage of their fears, the true source of the rumbling is revealed.